Insights and ideas Luyện kỹ năng đọc tiếng Anh - Ackert, Patricia. (Nxb Trẻ, 2000)
This is an engaging reading text for high-beginning through low-intermediate students of English as a foreign or second language. The text features 25 thematic units on a variety of topics, ranging from the culture specific to the universal.